2001
DOI: 10.1055/s-2001-15802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gum Resin of Boswellia serrata in Patients with Chronic Colitis

Abstract: Patients studied here suffered from chronic colitis characterized by vague lower abdominal pain, bleeding per rectum with diarrhoea and palpable tender descending and sigmoid colon. The inflammatory process in colitis is associated with increased formation of leukotrienes causing chemotaxis, chemokinesis, synthesis of superoxide radicals and release of lysosomal enzymes by phagocytes. The key enzyme for leukotriene biosynthesis is 5-lipoxygenase. Boswellic acids were found to be non-redox, non-competitive spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
214
0
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(230 citation statements)
references
References 0 publications
2
214
0
14
Order By: Relevance
“…Oral administration of a single dose of 1200 -1600 mg of ABAcontaining extract preparations yielded effective plasma concentrations of 2-32 M of various acetylated and nonacetylated boswellic acids (11,57,58), yet a high bioavailability of boswellic acids strongly depends on concomitant food intake (58). Treatment of glioblastoma patients with an extract from the gum resin of B. serrata, i.e., Indian frankincense, over 10 days led to a plasma levels of acetylated and nonacetylated forms of ␣-boswellic acid of 4 M (18).…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of a single dose of 1200 -1600 mg of ABAcontaining extract preparations yielded effective plasma concentrations of 2-32 M of various acetylated and nonacetylated boswellic acids (11,57,58), yet a high bioavailability of boswellic acids strongly depends on concomitant food intake (58). Treatment of glioblastoma patients with an extract from the gum resin of B. serrata, i.e., Indian frankincense, over 10 days led to a plasma levels of acetylated and nonacetylated forms of ␣-boswellic acid of 4 M (18).…”
Section: Discussionmentioning
confidence: 99%
“…by modulating DNA methylation in colorectal cancer cells Hon-Chiu E. Leung, 3 C. Richard Boland 1 and Ajay Goel DNA hypermethylation of CpG islands located within the promoter regions of tumor suppressor genes is a common epigenetic alteration involved in most human cancers. Unlike genomic epigenetic alterations, including aberrant methylation genes is potentially reversible with therapeutic agents.…”
Section: Boswellic Acid Induces Epigenetic Alterationsmentioning
confidence: 99%
“…[1][2][3][4][5] Acetyl-11-keto-β-boswellic acid (AKBA), one of the major active boswellic acids present in boswellia extracts, is a pentacyclic terpenoid, which has been shown to have antitumor effects in different types of tumor cells including colon, 6,7 prostate, 8,9 leukocytes, 10 liver 11 and brain. 12 Several earlier studies have reported inhibitory effects of AKBA on the nuclear factor kappa B (NFκB), 13 and the signal transducer and activator of transcription-3 (STAT-3)-related pathways, 14 which potentiate apoptosis and inhibit angiogenesis in neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Boswellia serrata contains four important BAs: a-boswellic acid, b-boswellic acid, 11-ketob-boswellic acid (KBA), and 3-acetyl-11-keto-b-boswellic acid (AKBA) (Singh et al, 1996). The gum resin is established to possess potent anti-inflammatory activity in traditional ayurvedic medicines (Ammon, 2006) and also used in other diseases like, joint pain (Sharma et al, 1989;Gupta et al, 1994;Kimmatkar et al, 2003), tumor (Huang et al, 2000), colitis (Gupta et al, 2001), hyperlipidemia (Pandey et al, 2005), crohn's illness (Gerhardt et al, 2001), etc.…”
Section: Introductionmentioning
confidence: 99%